Antihypertensive agents and the risk of breast cancer in women aged 55 years and older: a nested case-control study. Issue 3 (March 2016) - Chang, Chia-Hsuin; Chiang, Chien-Hsieh; Yen, Chung-Jen; Wu, Li-Chiu; Lin, Jou-Wei; Lai, Mei-Shu
Abstract : Objective: The study aimed to investigate the association of long-term use of different antihypertensive agents with incident breast cancer. Methods: A total of 794 533 women aged at least 55 years were identified from Taiwan National Health Insurance claims database during 2001–2011. As of 31 December 2011, incident breast cancer patients were included as cases, and 1 : 4 age-matched controls were selected by risk-set sampling scheme. Logistic regression models were applied to estimate the odds ratios (ORs) and 95% confidence intervals (CIs) of breast cancer incidence associated with different durations of use of angiotensin-converting enzyme inhibitors/angiotensin receptor blockers, β-blockers, and dihydropyridine calcium channel blockers (DHP CCBs). Different restriction rules were applied to reveal the potential effects of confounding by indication. Results: Among the 9397 incident breast cancer patients and 37 588 controls, a significantly elevated risk was found for relatively short-term use of DHP CCBs (<6 years) but not in those observed for more than 6 years. There was no association between either angiotensin-converting enzyme inhibitors/angiotensin receptor blockers or β-blockers use and breast cancer. Although restricting our analyses to those with any prescription of antihypertensive medications in 2001 or those with diagnosis of hypertension, there was no longer a statistically significant association between any use of DHP CCBs and breast cancer (OR: 1.21, 95% CI: 0.88–1.67 for the former, and OR: 1.71, 95% CI: 0.99–2.95 for the latter). Conclusion: The results demonstrated the potential effect of confounding by indication, and thus, did not suggest any association of the use of antihypertensive medication and breast cancer risk. Abstract : Supplemental Digital Content is available in the text